Tinjauan Kehujahan ‘Urf Terhadap Ijab Qabul dalam Perspektif Hukum Islam - Azni, Azni; Wahidin, Wahidin; Kurniawan, Rahmad; Jupendri, Ahmad (Al-Fikru: Jurnal Ilmiah, 2022)
One of the influences of customary tradition ('urf) in society is the matter of having to continue the ijab qabul lafaz in one breath. This started from the interpretation of ancient religious leaders and society in interpreting the opinion of one expert in Islamic law, namely Imam Syafi'i. This study aims to analyze the position of customary traditions ('urf) in Islamic law and the blasphemy of customary traditions ('urf) against Qabul's consent in continuous lafaz and one breath. The research method used is qualitative based on literature study. Primary data sources come from books of fiqh studies with the Shafi'i school as the main reference and secondary data sources come from relevant research results in the form of journal articles and final assignments, or books. The results of the study indicate that the validity of the customary tradition ('urf) on the implementation of the Ijab Kabul is still accepted as long as it does not conflict with Islamic law. Accepted in the sense that the act is jaiz (permitted) and does not defeat Islamic law, in the sense that it does not take over the position of the pillars of marriage and does not have to be forced to become a legal requirement for marriage, because its position is only a customary tradition ('urf) that has developed in society.